Online identity: constructing interpersonal trust and openness through participating in hospitality social networks - Ronzhyn, Alexander (Journal of Education Culture and Society, 2020)
The present article describes the results of research on online identity construction during the participation in the hospitality social networks. Specifi cally the user references are analy-sed to understand patterns that form the image of a member. CouchSurfi ng service (couch-surfi ng.org) allows users to leave short texts where the experience of hosting/being hosted by a CS member is described, is an evaluation of the CS members of each other’s personal traits, skills and common experience. Therefore references can become a good instrument for portraying a CouchSurfi ng member and understanding his or her particular traits. Refe-rences form an important part of a user’s virtual identity in the network. Using a sample of references of Spanish CouchSurfi ng users, the research established main characteristics of the references, which are the openness, readiness to share ideas and experiences and trustworthi-ness. These concepts illustrate the typical traits associated with a user of the network and also shed light on the activities common during offl ine CS meetings